Prospective randomize-controlled comparison between silicone plus herbal extract gel versus Aloe vera gel for burn scar prophylaxis - Kris Keorochana (2018)
© 2015 Elsevier GmbH. This study was to determine the effects of topical silicone plus herbal extract gel in comparison with Aloe vera gel in preventing scar formation after dermal burn. 70 patients were included in this study had dermal burns which are able to heal without skin grafts. The patients were randomized into two treatment groups: topical silicone plus herbal extract gel group (study group) and A. vera gel group (control group). Two (2) physicians, who do not know which treatment method was used, examined all subjects for 24 weeks from the date of wound healed. Post-burn scar was graded using the Modified Vancouver scar scale (MVSS - with the following parameters: pigmentation, vascularity, height, pliability, itching and pain) and the results from both groups were compared using T-test. Total MVSS were different in the two treatment groups and was statistically significant from week 12 (. p<. 0.05). The pigmentation and vascularity scores in the study group were significantly lower than control group at week 16 (. p<. 0.05). There were no statistical differences in pain and height between both groups (. p>. 0.05). In conclusion, the silicone plus herbal extract gel appears to be superior to A. vera gel in prevention of hypertrophic scars formation.